Hypoxia Promotes Mitochondrial Complex I Abundance via HIF-1α in Complex III and Complex IV Deficient Cells - Amy Saldana-Caboverde; Nadee Nissanka; Sofia Garcia; Anne Lombès; Francisca Diaz (Cells, 2020)
Murine fibroblasts deficient in mitochondria respiratory complexes III (CIII) and IV (CIV) produced by either the ablation of Uqcrfs1 (encoding for Rieske iron sulfur protein, RISP) or Cox10 (encoding for protoheme IX farnesyltransferase, COX10) genes, respectively, showed a pleiotropic effect in complex I (CI). Exposure to 1–5% oxygen increased the levels of CI in both RISP and COX10 KO fibroblasts. De novo assembly of the respiratory complexes occurred at a faster rate and to higher levels in 1% oxygen compared to normoxia in both RISP and COX10 KO fibroblasts. Hypoxia did not affect the levels of assembly of CIII in the COX10 KO fibroblasts nor abrogated the genetic defect impairing CIV assembly. Mitochondrial signaling involving reactive oxygen species (ROS) has been implicated as necessary for HIF-1α stabilization in hypoxia. We did not observe increased ROS production in hypoxia. Exposure to low oxygen levels stabilized HIF-1α and increased CI levels in RISP and COX10 KO fibroblasts. Knockdown of HIF-1α during hypoxic conditions abrogated the beneficial effect of hypoxia on the stability/assembly of CI. These findings demonstrate that oxygen and HIF-1α regulate the assembly of respiratory complexes.